Suspending Group Debate and Developing Concepts. (1st September 2013) - Stam, Daan; de Vet, Arne; Barkema, Harry G.; De Dreu, Carsten K. W.
Abstract : The ability of new product development (NPD) teams to generate ideas and develop high‐quality concepts for new products is a crucial determinant of NPD success. Although prior research in this area has developed various interventions to enhance the ability of teams to generate ideas, such interventions have limited impact on innovation management theory and practice. Partly, this is because of practical reasons: The interventions are often costly and impractical. However, there are also more fundamental, theoretical issues regarding these interventions: Knowledge of which interventions are effective in what situations is lacking. Even more importantly, there is no theory (or empirical evidence) about the effects of these interventions on the success of developing initial ideas into concepts. Together, this has caused the usefulness of these interventions for NPD teams to be uncertain at best. To remedy this situation, this study focuses on a costless and easy‐to‐implement intervention: suspending group debate. Suspending group debate refers to a team idea generation and concept development process in which groups debate a problem, ideas for solutions are generated individually, and these ideas are debated and developed into concepts collectively. The authors developed a new theory about the impact of suspending group debate on idea generation and on further concept development. Specifically, they argue that suspending group debate causes groups to generate a higher number of ideas, a higher number of original ideas, and a more diverse set of ideas, but that only the number of original ideas and the diversity of the set of ideas will translate into higher concept quality. The authors also developed new theory about when suspending group debate is especially effective. Specifically, they argue that suspending group debate is especially effective when at least one group member is low on extraversion. This theory is tested using an experimental design in which groups generated ideas and developed concepts for a specific organizational problem. Some groups suspend group debate, while others do not. Results show that suspending group debate indeed causes groups to generate a higher number of ideas, a higher number of original ideas, and a more diverse set of ideas. Importantly, results demonstrate that the effects of suspending group debate are more pronounced for groups with one or more group members that are low on extraversion. Furthermore, suspending group debate also affects concept quality, mediated by the number of original ideas and the diversity of ideas that groups generate (and thus not by the sheer number of ideas generated). Specifically, results show that both the diversity of the idea set as well as the number of original ideas positively influence the innovativeness of the final concept, while only the diversity of the idea set influences the comprehensiveness of the final concept.